2020
DOI: 10.1016/j.ebiom.2020.102663
|View full text |Cite
|
Sign up to set email alerts
|

White matter injury after neonatal encephalopathy is associated with thalamic metabolite perturbations

Abstract: Background: Although thalamic magnetic resonance (MR) spectroscopy (MRS) accurately predicts adverse outcomes after neonatal encephalopathy, its utility in infants without MR visible deep brain nuclei injury is not known. We examined thalamic MRS metabolite perturbations in encephalopathic infants with white matter (WM) injury with or without cortical injury and its associations with adverse outcomes. Methods: We performed a subgroup analysis of all infants recruited to the MARBLE study with isolated WM or mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…White matter injury was also evaluated for the cumulative model but did not reach significance, which is in line with a recent study revealing that white matter injury had the lowest specificity of the MRI biomarkers evaluated, with only 7% of the infants with white matter injury developing NDI at 2 years. 20 Previous studies have revealed that deep gray matter injury, such as bilateral basal ganglia changes, has an 84% sensitivity but a 42% specificity for death or central motor deficit at 1 year, 21 although diffusion imaging of the basal ganglia and thalamus has revealed much higher specificities for death or NDI of 95% and 98%, respectively. 22 Additionally, MRS has been evaluated as a prognostic biomarker, and deep gray matter lactate to N-acetyl aspartate ratio is one of the most accurate quantitative magnetic resonance biomarkers in the neonatal period for predicting NDI.…”
Section: Discussionmentioning
confidence: 99%
“…White matter injury was also evaluated for the cumulative model but did not reach significance, which is in line with a recent study revealing that white matter injury had the lowest specificity of the MRI biomarkers evaluated, with only 7% of the infants with white matter injury developing NDI at 2 years. 20 Previous studies have revealed that deep gray matter injury, such as bilateral basal ganglia changes, has an 84% sensitivity but a 42% specificity for death or central motor deficit at 1 year, 21 although diffusion imaging of the basal ganglia and thalamus has revealed much higher specificities for death or NDI of 95% and 98%, respectively. 22 Additionally, MRS has been evaluated as a prognostic biomarker, and deep gray matter lactate to N-acetyl aspartate ratio is one of the most accurate quantitative magnetic resonance biomarkers in the neonatal period for predicting NDI.…”
Section: Discussionmentioning
confidence: 99%
“…This might provide new insights for treating HIBD. Currently, hypothermia therapy is the only approved treatment method, but its high cost and uncertain prognostic effects remain a concern (Ranjan and Gulati, 2023;Thayyil et al, 2023). Treatment starting within 6 h shows neuroprotective effects, posing a huge challenge for early diagnosis of HIBD.…”
Section: Figurementioning
confidence: 99%
“…During development, grey and white matter injuries have been associated with sub-acute and chronic hypoxia-ischemia. Importantly, white matter injury is common in pre-term babies; however, results are contrasting in term babies, in whom white matter injury has been linked with chronic hypoxia, but not in areas of high metabolic activity like the thalamus [ 118 ]. These differences in white matter injury in pre-term and term babies may be a reflection on the maturation of oligodendrocytes in pre-term and full-term babies [ 69 ].…”
Section: Contributions Of Central and Peripheral Cells To Neonatalmentioning
confidence: 99%